2020
DOI: 10.3390/app10031173
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Nondestructive Discrimination of Geographical Origins of Longjing Tea using Hyperspectral Imaging at Two Spectral Ranges Coupled with Machine Learning Methods

Abstract: Longjing tea is one of China’s protected geographical indication products with high commercial and nutritional value. The geographical origin of Longjing tea is an important factor influencing its commercial and nutritional value. Hyperspectral imaging systems covering the two spectral ranges of 380–1030 nm and 874–1734 nm were used to identify a single tea leaf of Longjing tea from six geographical origins. Principal component analysis (PCA) was conducted on hyperspectral images to form PCA score images. Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…Decision tree (DT), support vector regression (SVR) and radial basis function neural network (RBFNN) have a strong ability to deal with nonlinear issues. These methods combined with spectral technology have achieved good results in detection of crop diseases [37], determination of crop origins [38,39] and prediction of physiological indexes [40,41]. It confirms the superiority of machine learning in mining the relationship between variables.…”
Section: Introductionmentioning
confidence: 60%
“…Decision tree (DT), support vector regression (SVR) and radial basis function neural network (RBFNN) have a strong ability to deal with nonlinear issues. These methods combined with spectral technology have achieved good results in detection of crop diseases [37], determination of crop origins [38,39] and prediction of physiological indexes [40,41]. It confirms the superiority of machine learning in mining the relationship between variables.…”
Section: Introductionmentioning
confidence: 60%
“…SVM, based on the statistical learning theory and structural risk minimization, is a supervised classification method which can deal with both linear and nonlinear data efficiently with good generalization ability [25,26]. Compared with other methods, SVM has such advantages as it does not need a large number of training samples for developing a model and is not affected by the presence of outliers [27] and has been proven as a reliable and efficient method for the spectral data analysis of agricultural products [28][29][30][31][32]. Artificial neural networks have been widely used in agriculture areas, including surface inspection of fruits [17,[33][34][35][36][37][38], since regaining their popularity in the early 1980s.…”
Section: Classification Methodsmentioning
confidence: 99%
“…Therefore, when establishing a regiontracing model, eliminating the influence of the time factor will help avoid the case that the model based on samples from a specific year could not be successfully applied to predict samples from next year. Moreover, Hong et al (112) used HSI systems covering the two spectral ranges of 380-1,030 nm (VIS/NIR) and 874-1,734 nm (NIR) to classify Longjing tea from six geographical origins. The results indicated that the PLS-DA model had better performance with VIS/NIR (accuracy of 91.98%) than PLS-DA with NIR (accuracy of 84.89%).…”
Section: Beveragementioning
confidence: 99%